Curves in Multiplicative Equiaffine Space - Ogrenmis, Meltem; Ogrenmis, Alper Osman (Mdpi, 2025)
In this study, the geometric properties of curves in multiplicative equiaffine space are investigated using multiplicative calculus. Fundamental geometric concepts such as multiplicative arc length, multiplicative equiaffine curvature, and torsion are introduced. This study derives the multiplicative Frenet frame and associated Frenet equations, providing a systematic framework for describing the geometric behavior of multiplicative equiaffine curves. Additionally, curves with constant multiplicative curvature and torsion are characterized and supported with illustrative examples.
Keywords: affine space; equiaffine space curves; multiplicative calculus; multiplicative derivative; multiplicative integral